STRATEGI KOMUNIKASI DALAM PEMBELAJARAN UNTUK MENGATASI KECEMASAN KOMUNIKASI MAHASISWA UNIKA SANTU PAULUS RUTENG, MANGGARAI, NUSA TENGGARA TIMUR - Yohanes Wendelinus Dasor; Stanislaus Hermaditoyo; Robertus Hudin (CV. Pusdikra Mitra Jaya, 2022)
Communication anxiety is a tendency to experience anxiety when trying to communicate in a certain situation. Within the scope of education, communication anxiety affects the academic achievement of students. Therefore, this study aims to describe communication strategies in learning to overcome communication anxiety. The method used in this research is descriptive qualitative. The stages that are passed include: first, measuring the level of student communication anxiety. Second, identify the factors that cause student communication anxiety. Third, designing communication strategies in learning to overcome student communication anxiety. Based on the research findings, it is known that: first, the majority of UNIKA Santu Paulus Ruteng students are at the level of communication anxiety in the medium category. A total of 3.32% are in a very high level of anxiety and as many as 30.16% are not experiencing communication anxiety. Second, the causes of student communication anxiety are influenced by internal factors and external factors. Internal factors include knowledge, skills and self-concept. While external factors include environmental motivation, past experiences, learning from parents, communication situations and assessment factors. Third, because there are learning strategies that can be applied to overcome communication anxiety in students, among others, through creating a pleasant learning atmosphere, accompanied by humor and not tense; the use of student-centered learning methods; build relationships/closeness with students; and adheres to the principle of flexibility in the learning process.